ЗОВНІШНЬОПОЛІТИЧНИЙ ФАКТОР У ПРОЦЕСІ ФОРМУВАННЯ КУПЕЦТВА ПІВДЕННОЇ УКРАЇНИ В ПЕРШІЙ ПОЛОВИНІ ХІХ СТОЛІТТЯ (Zaporizhzhia Historical Review, 2021)
The present publication emphasizes the role of foreign affairs factor in the process of the trade formation in South Ukraine in the first part of 19 century. Foreign policy was essential for this region in terms of economical life of the area. Hostilities during numerous Russian-Turkish campaigns and trade blockade prevented traditional business relations. Along with this they were creating a new sphere for the trade activity, namely, cattle, provision and cloth supply for the Russian army.